Sarcoidosis with the livedo reticularis-like appearance: Sarcoidosis livedo - Wang, Yu-Feng; Song, Chun-Xiao; Tan, Cheng (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Sarcoidosis is a multisystem inflammatory disease manifesting as noncaseating epithelioid cell granulomas. 25 to 30% of individuals with systemic sarcoidosis show variable cutaneous manifestations. A 59-year-old female was seen with reticular purplish-red nodules and plaques on the legs for three months. A skin biopsy of the livedo area revealed non-caseating epithelioid cell granulomas surrounding blood vessels in the dermis. She was diagnosed with sarcoidosis livedo, and cutaneous lesions subsided with oral prednisone. Sarcoidosis livedo (SL) assumes a uncommon livedo reticularis-like presentation. This is the first Chinese patient with SL, and more patients are needed to unveil the unique characters of SL.